Recent advances in computed tomography radiation dosimetry - Sarhan, Hatan Ghazi; Noor, Noramaliza; Mohamed Saini, Suraini; Bahari, Norafida (Longe Medikal Sdn. Bhd, 2023)
Computer tomography (CT) has proved fundamental in image evaluation throughout the past three decades. By combining rapid scanning with high-quality data sets, multi-detector technology continues to influence practice patterns. This has led to new applications and improved use in conventional applications. However, the increased use of CT has generated significant concern regarding the high radiation doses received by patients during CT scans compared to traditional radiography examinations. Many studies have been undertaken on minimizing patient dose and adhering to the as low as reasonably achievable (ALARA) principle. A total of 40 English articles from PubMed, Science Direct and Google Scholar were systematically summarized in this review paper to introduce the growth of CT scan from single-slice to multi-slice technology from 2000 until December 2020 as well as dual-energy and multi-detector CT technologies. The important role of utilizing CT radiation dosimeters for CT dose measurement is defined included CT dose reduction techniques.